Anaerobic power profile: Talent-selected femail gymnasts age 9-11 - Sands, W. M.; McNeal, J. R.; Jemni, M. (Technique, 2001)
The purpose of this study was to descriptively characterize the anaerobic power and capacity of young talent-selected female gymnasts. A repeated jumps test was chosen to explore anaerobic power and capacity in an effort to simulate the dominant skills of gymnastics. Sixty-three female gymnasts between 9-12 years old participated in the study. The gymnasts performed a test of repeated jumps for 60 seconds with controlled knee flexion during landing and hands constrained to grasping the waist throughout the test. Data were collected via custom computer software, apparatus, and interface. Results showed that the gymnasts reached peak average power during the 10-20 second time interval. Mean total average power was 28.4 W/kg. No statistically significant difference between age groups, between test time intervals, nor the interaction were found. The results of this study indicate these young gymnasts were more powerful than their Senior National Team counterparts, and that the power values were dramatically higher than those obtained by Wingate-type tests. We conclude that repeated jumps-type tests are worthy of further research.